2020
DOI: 10.1002/aic.17103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations on the hydration and underwater oleophobicity of zwitterionic self‐assembled monolayers

Abstract: Zwitterionic materials have attracted increasing attentions in the underwater super‐oleophobic applications for its strong hydration via electrostatic interactions. Herein, molecular dynamics simulations were used to investigate the hydration and underwater oleophobicity of sulfobetaine‐terminated self‐assembled monolayers (SB‐SAMs) with different carbon spacer lengths (CSL) between oppositely charged groups of SB molecules. Simulation results show that the hydration of SB‐SAMs is positively dependent on CSL; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…All these results are in accordance with previous simulations studies of bulk water. 37,38 As suggested by Chen et al, 42 the fact that the RDF does not converge to 1 is due to the solid− liquid interface and to the inhomogeneous ion distributions in the simulation systems.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…All these results are in accordance with previous simulations studies of bulk water. 37,38 As suggested by Chen et al, 42 the fact that the RDF does not converge to 1 is due to the solid− liquid interface and to the inhomogeneous ion distributions in the simulation systems.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Until the salt concentration continues to increase, the size of the nanopore changes slightly. Liao et al 75 and Chen et al 47 explored the effect of ionic strength with NaCl salt on the underwater oleophobicity of a zwitterionic system. They found that the addition of salt weakened the self-association between zwitterion molecules, which led to the enhancement of hydration, which indicated the improvement of antifouling properties.…”
Section: Salt Concentration-controlled Pore Open/closurementioning
confidence: 99%
“…Computer simulations can supplement the experimental work and facilitate the exploration of new achievements. 47,48 Nevertheless, some computer simulation studies have been carried out to explore the nanopore properties, and the structure-activity relationship is not well understood [49][50][51] for zwitterion-modified nanopores. Owing to the fact that physical phenomena observed at the macroscopic scale are essentially determined by the microstructure of matter, mesoscopic simulation actually serves as a bridge between molecular information and macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been used to evaluate the dynamic and static properties of water molecules in the vicinity of polymer side chains. These studies have focused specifically on hydration structures and the microscopic behavior of water molecules in this region. Kuo et al conducted MD simulations to investigate the water structures of hydrated PMEA, the results of which indicated that bound water in polymers with better biocompatibility possesses higher mobility.…”
Section: Introductionmentioning
confidence: 99%